A prospective study of arteriovenous fistula failure in a tertiary teaching hospital of Andhra Pradesh, India - Kumar Mohapatra, Sanjay; Hari Prasad Rao, Dumpala (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2020)
Background: An arteriovenous (AV) fistula is an abnormal connection between an artery and a vein. Normally, blood flows from your arteries to your capillaries to your veins. Nutrients and oxygen in your blood travel from your capillaries to tissues in your body. With an arteriovenous fistula, blood flows directly from an artery into a vein, bypassing some capillaries. When this happens, tissues below the bypassed capillaries receive diminished blood supply. Arteriovenous fistula (AVF) is the preferred access for hemodialysis in patients with chronic kidney disease. This study aimed to report the outcomes and common complications of AVF. Methodology: A prospective, study was conducted on 120 patients on hemodialysis in the Department of Surgery GEMS Srikakulam from February-November 2017. The failure rates, complications, and outcomes were assessed in this study. Results: A total of 120 AVF fistulae were created. It was radiocephalic in 94 cases and brachial fistula in 26 cases all of which were constructed in an end-side fashion. AVF maturation was seen in n=105 (87.5%) with the majority occurring in the first 6 weeks with a failure rate of 12.5 % (n=15) who were excluded from the further follow-up. Conclusion: Complications developed in 27.5% (n=33) of patients who were managed appropriately.